Green leafhopper in crops of Jatropha curcas in Mato Grosso do Sul State, Brazil - NONATO DE OLIVEIRA, HARLEY; DA SILVA, CÉSAR JOSÉ; ABOT, ALFREDO RAUL; ARAÚJO, DANIELE INOCÊNCIO (Revista Colombiana de Entomología, 2010)
The objective of this work was to report the occurrence of Empoasca kraemeri in plantations of physic nut (Jatropha curcas) in Mato Grosso do Sul, in the municipalities of Anastácio, Chapadão do Sul, Dourados, Eldorado, Nova Andradina and Rio Brilhante. Nymphs and adults of this leafhopper were observed on leaves of the plants. In addition to this report, the population dynamics of the leafhopper were evaluated from March 2008 until February 2009, through sticky traps installed in areas with physic nut plantations from Embrapa Agropecuária Oeste, in Dourados, MS. The greatest populations were observed in February, March, April, May and June, with an absence of insects from August to November. In the periods of greatest occurrence, yellowing and deformity of the leaves was verified. Knowledge of the leafhopper’s population peaks will be an important component for defining strategies for its management.